LPS-Induced Lung Inflammation in Marmoset Monkeys – An Acute Model for Anti-Inflammatory Drug Testing - Seehase, Sophie; Lauenstein, Hans-Dieter; Schlumbohm, Christina; Switalla, Simone; Neuhaus, Vanessa; Förster, Christine; Fieguth, Hans-Gerd; Pfennig, Olaf; Fuchs, Eberhard; Kaup, Franz-Josef; Bleyer, Martina; Hohlfeld, Jens M.; et al. (PloS one, 2012)
Increasing incidence and substantial morbidity and mortality of respiratory diseases requires the development of new human-specific anti-inflammatory and disease-modifying therapeutics. Therefore, new predictive animal models that closely reflect human lung pathology are needed. In the current study, a tiered acute lipopolysaccharide (LPS)-induced inflammation model was established in marmoset monkeys (Callithrix jacchus) to reflect crucial features of inflammatory lung diseases. Firstly, in an ex vivo approach marmoset and, for the purposes of comparison, human precision-cut lung slices (PCLS) were stimulated with LPS in the presence or absence of the phosphodiesterase-4 (PDE4) inhibitor roflumilast. Pro-inflammatory cytokines including tumor necrosis factor-alpha (TNF-α) and macrophage inflammatory protein-1 beta (MIP-1β) were measured. The corticosteroid dexamethasone was used as treatment control. Secondly, in an in vivo approach marmosets were pre-treated with roflumilast or dexamethasone and unilaterally challenged with LPS. Ipsilateral bronchoalveolar lavage (BAL) was conducted 18 hours after LPS challenge. BAL fluid was processed and analyzed for neutrophils, TNF-α, and MIP-1β. TNF-α release in marmoset PCLS correlated significantly with human PCLS. Roflumilast treatment significantly reduced TNF-α secretion ex vivo in both species, with comparable half maximal inhibitory concentration (IC(50)). LPS instillation into marmoset lungs caused a profound inflammation as shown by neutrophilic influx and increased TNF-α and MIP-1β levels in BAL fluid. This inflammatory response was significantly suppressed by roflumilast and dexamethasone. The close similarity of marmoset and human lungs regarding LPS-induced inflammation and the significant anti-inflammatory effect of approved pharmaceuticals assess the suitability of marmoset monkeys to serve as a promising model for studying anti-inflammatory drugs.